Bridging the collectives: A review of collective human–robot construction. (December 2021) - Han, Isla Xi; Meggers, Forrest; Parascho, Stefana
Advancements in multi-agent, autonomous, and intelligent robotic systems over the past decades point toward new design and fabrication possibilities. Exploring how humans and robots can create and construct collectively is essential in leveraging robotic technology in the building sector. However, only by making existing knowledge from relevant technological disciplines accessible to designers can we fully exploit current construction methods and further develop them to address the challenges in architecture. To do this, we present a review paper that bridges the gap between Collective Robotic Construction (CRC) and Human–Robot Interaction (HRI) and defines a new research domain in Collective Human–Robot Construction (CHRC) in the architectural design and fabrication context.